The Correlation between Parents’ Personalities and Responsible Environmental Behavior on Students’ Learning at School - Karnadi, Karnadi; Sudarwanto, Sudarwanto; Rismayati, Ade Imas (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
Environment is everything around the human being and influences the development of human life. Environmental problems have to be solved by all parties, including parents. Environmental responsibility behavior comes from an awareness of the problems that occurred. This awareness can solve the problems. The responsibility behavior of parents is the result of the interaction of various factors, one of them is a personality factor. This study aimed to recognize the correlation between personality and environmental responsibility behavior of parents. This research was conducted in SMP (Junior High School) Labschool Jakarta, SMP Labschool Kebayoran, and SMP Labschool Cibubur in the first semester of the 2019/2020 academic year. The population of the study was all parents whose children study at the mentioned Lab schools. The method used was a survey method through correlational studies. The correlation coefficient obtained was 0.961. It could be interpreted that the determination coefficient was 92.4 %. Based on the result, it could be concluded that the personality variable contributed to the parents’ environmental responsibility behavior (92.4 %) while 7.6 % was determined by other factors. The very high correlation could have an impact on a child's parenting. Parents who have a high personality will educate their children to have a high personality and environmental responsibility as well. Learning models in schools that are appropriate and contain strong Islamic values will be able to strengthen the personality of a child that has been formed by his parents at home.